'Perplex'd in extreme', or (in)fidelity in translation : Reading and performing Shakespeare in contemporary Argentina - Montezanti, Miguel Angel (2005)
The purpose of this article is to illustrate the reception of some Shakespearean plays in Argentina. Part 1 focuses on the limitations imposed by the audience's moral taste upon the translator's choices. Part 2 analyzes two cases in which source language (SL) texts have been heavily transformed, i.e., "appropriated" by two Argentine contemporary playwrights.
Documento incorporado en 2019 en el marco del "Programa de becas de experiencia laboral" de la Biblioteca Guillermo Obiols para estudiantes de Bibliotecología, a partir de un procedimiento técnico de captura de datos desarrollado por el personal del IdIHCS.
Keywords: Shakespeare, William; Análisis literario; Argentina; Siglo XX